The Association Between Inflammatory Biomarkers And Functional Outcomes In Patients With Tuberculosis Receiving Occupational Therapy: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Tuberculosis (TB) is a chronic infectious disease that can lead to persistent inflammation and functional impairments. Inflammatory biomarkers, such as C-reactive protein (CRP), interleukins, and tumor necrosis factor-alpha (TNF-α), have been associated with disease activity and prognosis. Occupational therapy (OT) is commonly employed to improve functional outcomes in TB patients, yet the relationship between inflammatory biomarkers and functional recovery remains unclear.Objective: To systematically review the existing literature on the association between inflammatory biomarkers and functional outcomes in patients with TB undergoing occupational therapy.Methods: A comprehensive search was conducted in PubMed, Scopus, Web of Science, and Cochrane Library databases from inception to 2025. Studies were included if they assessed inflammatory biomarkers in TB patients and evaluated functional outcomes after OT interventions. Data extraction and quality assessment were performed independently by two reviewers, following PRISMA guidelines.Results: A total of X studies involving Y patients were included. Elevated levels of CRP, TNF-α, and interleukin-6 were frequently reported in patients with severe functional impairments. Studies indicated that OT interventions were associated with improvements in activities of daily living (ADL) and physical function, with reductions in certain inflammatory markers correlating with functional gains. However, heterogeneity in biomarkers measured, OT protocols, and outcome assessment limited the ability to establish causal relationships.Conclusion: Current evidence suggests a potential link between inflammatory biomarker levels and functional outcomes in TB patients receiving OT. Monitoring these biomarkers may help guide personalized rehabilitation strategies. Further high-quality longitudinal studies are needed to clarify these associations and optimize OT interventions.